West Virginia University : Symbol of Unity in a Sectionalized State - Doherty, William T.; Summers, Festus P. (Festus Paul), 1895-1971 (Book collections on Project MUSE., 2013)
Details the history of WVU from before its inception as the Agricultural College of West Virginia in 1867 to its expansion and development in the 1980s. This comprehensive history includes an index of people, places and events; photographs and illustrations; and in-depth descriptions of campuses, buildings, colleges, and academic and sports programs. A joint effort between William T Doherty, Jr., a Professor Emeritus History at WVU and Festus P. Summers, the first University Librarian who passed away before this project was complete, this new edition once again grants access to the diverse and complex elements which shaped the institution.